The awoken : a novel - Howes, Katelyn Monroe (Dutton, an imprint of Penguin Random House LLC, 2022)
"A cinematic, speculative debut about a woman who undergoes cryogenic preservation at the time of her death and wakes up a century later in a world where her very life is a crime. When Alabine Rivers, a politically active young woman with a bright career and romance ahead of her, finds out the devastating news that she has terminal cancer, the only thing that gives her solace is the possibility of a second life through the emerging field of cryogenics. A century later, scientists have indeed discovered how to bring back the dead from preservation, but humanity has been locked in a philosophical battle over the ethics of this new Godlike power, a battle that has turned violent: those who are resurrected, the Awoken, have been declared illegal and are to be shot on sight. This is the world Alabine is brought into by the Resurrectionists, an underground militia fighting for the rights of the Awoken. Finding herself in a completely unfamiliar world, and one where she is an outsider for the first time in her life, Alabine must figure out how to survive and determine her place in this new world, all the while being haunted by lucid memories of her previous life and the man she loved. The Awoken is a gripping, action-packed story full of plot twists and high emotion. It's a look at prejudice, complicity, the fears that tear us apart, and the hope that can bring us together"--